Assessment of Treatment Response by 99mTc-MIP-1404 SPECT/CT: A Pilot Study in Patients With Metastatic Prostate Cancer. (August 2018) - Schmidkonz, Christian; Cordes, Michael; Beck, Michael; Goetz, Theresa Ida; Schmidt, Daniela; Prante, Olaf; Bäuerle, Tobias; Cavallaro, Alexander; Uder, Michael; Wullich, Bernd; Goebell, Peter; Kuwert, Torsten; et al.
Abstract : Background: We investigated the role of 99m Tc-MIP-1404 (Progenics Pharmaceuticals, Inc, New York, NY) SPECT/CT of PSMA expression in the assessment of treatment response in patients with metastatic prostate cancer. Methods: We retrospectively analyzed 99m Tc-MIP-1404 SPECT/CT scans from 28 patients with metastatic prostate cancer examined before initiation and after completion of therapy. Eight of these patients had been treated with androgen deprivation therapy, 10 with docetaxel, and another 10 with external beam radiotherapy. On the CT images from SPECT/CT, treatment response was assessed according to RECIST 1.1 criteria; independently from that analysis, maximal standardized uptake values (SUVmax ) were quantified in representative tumor lesions and treatment response assumed at differences in SUVmax greater than 30%. Radiographic response assessment was correlated to biochemical response (BR) based on prostate-specific antigen serum levels. Results: The concordance rate between SPECT and BR was 75% (95% confidence interval [CI], 0.55–0.89) (Cohen κ = 0.57; 95% CI, 0.29–0.85; P ⩽ 0.01), higher than for that between SPECT and CT with 57% (95% CI, 0.37–0.76) (κ = 0.40; 95% CI, 0.14–0.65; P ⩽ 0.01), as well as that between CT and BR with 50% (95% CI, 0.31–0.69) (κ = 0.31; 95% CI, 0.06–0.57, P ⩽ 0.05). Discordant findings between SPECT and CT were most likely due to limitations of CT in assessing metastases in lymph nodes, as well as bone involvement, which was sometimes not detectable on CT scans. Conclusions: The high agreement between treatment response, as assessed by 99m Tc-MIP-1404 SPECT/CT and BR, suggests a possible role of that imaging tool for monitoring treatment in metastatic prostate cancer. Larger, ideally prospective trials are needed to help to reveal the full potential of SPECT imaging of PSMA expression in that regard.